1991
DOI: 10.1007/bf00317600
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of vesicular-arbuscular mycorrhizae during old field succession

Abstract: The species composition of vesicular-arbuscular mycorrhizal (VAM) fungal communities changed during secondary succession of abandoned fields based on a field to forest chronosequence. Twenty-five VAM fungal species were identified. Seven species were clearly early successional and five species were clearly late successional. The total number of VAM fungal species did not increase with successional time, but diversity as measured by the Shannon-Wiener index tended to increase, primarily because the community be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
1
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(156 citation statements)
references
References 39 publications
14
138
1
3
Order By: Relevance
“…Since soil pathogens can reduce survival of tree seedlings (Augspurger 1984;Packer and Clay 2000) and reduce the abundance of trees relative to herbaceous vegetation (Weste 1986), it is possible that pathogenic infection rates differed between the non-indigenous and native grass subplots. At Cedar Creek, Johnson et al (1991) found that different grass species support different the communities of vesicular-arbuscular mycorrhizal (VAM) fungi, and, in particular, that VAM fungi communities differed between garden plots composed of Schizachyrium scoparium and Poa pratensis, respectively (Johnson et al 1992). Thus, another possible explanation for the survival differences between the two grass functional groups could involve differences in VAM fungi communities in the non-indigenous and native grass subplots that may have affected nutrient and/or water uptake by the seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Since soil pathogens can reduce survival of tree seedlings (Augspurger 1984;Packer and Clay 2000) and reduce the abundance of trees relative to herbaceous vegetation (Weste 1986), it is possible that pathogenic infection rates differed between the non-indigenous and native grass subplots. At Cedar Creek, Johnson et al (1991) found that different grass species support different the communities of vesicular-arbuscular mycorrhizal (VAM) fungi, and, in particular, that VAM fungi communities differed between garden plots composed of Schizachyrium scoparium and Poa pratensis, respectively (Johnson et al 1992). Thus, another possible explanation for the survival differences between the two grass functional groups could involve differences in VAM fungi communities in the non-indigenous and native grass subplots that may have affected nutrient and/or water uptake by the seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a trend of species diversity of AMF being negatively correlated with plant species diversity along the successional gradient. Data from a temperate region showed that AMF diversity tended to increase with successional rank in an old field succession (Johnson et al 1991), while fungal diversity was relatively uniform in a desert ecosystem despite the diversity in the plant community (Bethlenfalvay et al 1984). Increase in AMF species richness was accompanied by an increase in plant diversity and ecosystem productivity in simulated macrocosms of temperate ecosystems (van der Heijden et al 1998).…”
Section: Number Of Viable Sporesmentioning
confidence: 99%
“…Even though 6 genera and more than 145 species of AM fungi are currently recognized based on their spore morphologies (Morton & Bentivenga, 1994), the bits of evidence that have accumulated to date suggest that AM fungi are far more genetically diverse (Sanders et al, 1996) and functionally diverse (Johnson, Zak & Tilman, 1991 ;Sanders & Fitter, 1992 a, b, c ;Sanders, 1993 ;Hamel et al, 1994) than originally suspected. Given that this diversity exists, the real challenge is to categorize AM fungal taxa into functional groups to help us understand and, ultimately, manage disturbed ecosystems (Johnson & Wedin, 1997).…”
Section: mentioning
confidence: 99%